Improve Teaching Capacity at Private Universities in Ho Chi Minh City, Vietnam According to AUN-QA - Phan Quoc Lam; Vo Van Tuan; Duong Thi Thanh (International Journal of Cognitive Research in Science, Engineering and Education, 2020)
The purpose of this study was to develop an approach to assessing the potential of teachers for the possibility of introducing quality standards of the educational process according to AUN-QA in the higher education system of Vietnam. A survey of teachers and managers of 6 private universities in Ho Chi Minh City was carried out, aimed at assessing the quality of university teachers and their potential to AUN-QA standards. The number of respondents was 172 teachers and 42 managers of the studied universities. Evaluation of the survey responses was made on a 4-point Likert scale. Using the SPSS 22.0 software package, statistical processing of the results of the questionnaire survey of teachers was carried out. By means of questionnaires, an assessment of the need (urgency) and the possibility of implementing measures aimed at increasing the teaching potential was carried out. A pedagogical experiment was carried out, which involved the passage of training for teachers in order to increase the pedagogical potential: the development of the theoretical base and practical skills in the application of teaching methods, such as Teaching simulation, Teaching case studies, Learning project, Teaching by situation, Lecture, Problem solving, Teaching in groups, Practical methods, experiments, Training method, review. The experiment involved 61 teachers from Van Lang University. According to the results of the experiment, a statistically significant increase in the level of methodological knowledge of teachers and skills for their implementation was revealed. The results obtained are of practical importance and can serve as a basis for solving numerous problems of higher education in the country. They can also be used to improve the quality of educational services, the effectiveness of reforms in the education system of Vietnam.